HPA-axis stress reactivity in youth depression: evidence of impaired regulatory processes in depressed boys - Lopez-Duran, Nestor L. (Stress, 2015)
Given the link between youth depression and stress exposure, efforts to identify related biomarkers have involved examinations of stress regulation systems, including the hypothalamic–pituitary–adrenal (HPA) axis. Despite these vast efforts, the underlying mechanisms at play, as well as factors that may explain heterogeneity of past findings, are not well understood. In this study, we simultaneously examined separate components of the HPA-axis response (e.g. activation intensity, peak levels, recovery) to the Socially Evaluated Cold-Pressor Test in a targeted sample of 115 youth (age 9–16), recruited to overrepresent youth with elevated symptoms of depression. Among youth who displayed a cortisol response to the task, depression symptoms were associated with higher peak responses but not greater rate of activation or recovery in boys only. Among those who did not respond to the task, depression symptoms were associated with greater cortisol levels throughout the visit in boys and girls. Results suggest that depression symptoms are associated with a more prolonged activation of the axis and impaired recovery to psychosocial stressors primarily in boys. We discussed two potential mechanistic explanations of the link between depression symptoms and the duration of activation: (1) inhibitory shift (i.e. point at which the ratio of inhibitory and excitatory input into the axis shifts from greater excitatory to greater inhibitory input) or (2) inhibitory threshold (i.e. level of cortisol exposure required to activate the axis’ feedback inhibition system).